Glycotope sharing between snail hemolymph and larval schistosomes: larval transformation products alter shared glycan patterns of plasma proteins. - Timothy P Yoshino; Xiao-Jun Wu; Hongdi Liu; Laura A Gonzalez; André M Deelder; Cornelis H Hokke (Public Library of Science (PLoS), 2012)
Recent evidence supports the involvement of inducible, highly diverse lectin-like recognition molecules in snail hemocyte-mediated responses to larval Schistosoma mansoni. Because host lectins likely are involved in initial parasite recognition, we sought to identify specific carbohydrate structures (glycans) shared between larval S. mansoni and its host Biomphalaria glabrata to address possible mechanisms of immune avoidance through mimicry of elements associated with the host immunoreactivity. A panel of monoclonal antibodies (mABs) to specific S. mansoni glycans was used to identify the distribution and abundance of shared glycan epitopes (glycotopes) on plasma glycoproteins from B. glabrata strains that differ in their susceptibilities to infection by S. mansoni. In addition, a major aim of this study was to determine if larval transformation products (LTPs) could bind to plasma proteins, and thereby alter the glycotopes exposed on plasma proteins in a snail strain-specific fashion. Plasma fractions (< 100 kDa/> 100 kDa) from susceptible (NMRI) and resistant (BS-90) snail strains were subjected to SDS-PAGE and immunoblot analyses using mAB to LacdiNAc (LDN), fucosylated LDN variants, Lewis X and trimannosyl core glycans. Results confirmed a high degree of glycan sharing, with NMRI plasma exhibiting a greater distribution/abundance of LDN, F-LDN and F-LDN-F than BS-90 plasma (< 100 kDa fraction). Pretreatment of blotted proteins with LTPs significantly altered the reactivity of specific mABs to shared glycotopes on blots, mainly through the binding of LTPs to plasma proteins resulting in either glycotope blocking or increased glycotope attachment to plasma. Many LTP-mediated changes in shared glycans were snail-strain specific, especially those in the < 100 kDa fraction for NMRI plasma proteins, and for BS-90, mainly those in the > 100 kDa fraction. Our data suggest that differential binding of S. mansoni LTPs to plasma proteins of susceptible and resistant B. glabrata strains may significantly impact early anti-larval immune reactivity, and in turn, compatibility, in this parasite-host system.